The impact of ambidexterity on robotic process automation implementation strategy in service enterprises - Piotr Sliż; Jędrzej Siciński; Beata Jackowska (Future Business Journal)
Abstract Robotic Process Automation (RPA) has gained increasing significance in recent years. RPA leverages software bots to automate repetitive business processes traditionally performed by humans, making it one of the easiest, least invasive, and fastest automation approaches. Publications on the topic are scarce, however, and concerns regarding job loss and employee acceptance of new operational processes and technologies remain significant challenges. The additional motivation behind this study is to address the lack of research on the implementation strategy of RPA in the context of ambidexterity, i.e., optimizing enterprise capability in balancing between exploration and exploitation. The paper adopts a managerial perspective and aims to identify the key factors supporting the implementation of RPA in the context of ambidexterity, using an empirical study of service companies as an example. The research methodology employed includes literature review, opinion surveys, and statistical analysis. The paper highlights the stimulating role of the ambidexterity concept in RPA implementation projects and strategies, with a hybrid approach to dynamic balancing of exploitation and exploration. The findings of this paper will be of use for researchers and practitioners in developing effective RPA implementation strategies that balance the needs for exploitation and exploration while factoring in the concerns raised by employees.